Excavations at Fishbourne - Cunliffe, Barry (Reports of the Research Committee of the Society of Antiquaries of London, 1971)
This is an account of excavations of the Roman villa at Fishbourne, in the south of England, conducted in the 1960s. Included are descriptions of buildings and artefacts such as pottery, coins, interiors and metalwork, together with an account of the methodology used to unearth these.